Tumor-Specific Monomethyl Auristatin E (MMAE) Prodrug Nanoparticles for Safe and Effective Chemotherapy - Hanhee Cho; Man Kyu Shim; Yujeong Moon; Sukyung Song; Jinseong Kim; Jiwoong Choi; Jeongrae Kim; Youngjoo Lee; Jung Yeon Park; Yongju Kim; Cheol-Hee Ahn; Mi Ra Kim; et al. (MDPI AG, 2022)
A prodrug is bioreversible medication that is specifically converted to the active drugs by enzymes overexpressed in the tumor microenvironment, which can considerably reduce the chemotherapy-induced side effects. However, prodrug strategies usually have low antitumor efficacy compared to free drugs by delayed drug release. This is because they need time to be activated by enzymatic cleavage and they also cannot be fully recovered to the active drugs. Therefore, highly potent anticancer drug should be considered to expect a sufficient antitumor efficacy. Herein, we propose tumor-specific monomethyl auristatin E (MMAE) prodrug nanoparticles for safe and effective chemotherapy. The cathepsin B-specific cleavable FRRG peptide and MMAE are chemically conjugated via one-step simple synthetic chemistry. The resulting FRRG-MMAE molecules form stable nanoparticles without any additional carrier materials by hydrophobic interaction-derived aggregations. The FRRG-MMAE nanoparticles efficiently accumulate within the tumor tissues owing to the enhanced permeability and retention (EPR) effect and inhibit the tubulin polymerization by releasing free MMAE in the cathepsin B-overexpressed tumor cells. In contrast, FRRG-MMAE nanoparticles maintain a non-toxic inactive state in the normal tissues owing to innately low cathepsin B expression, thereby reducing MMAE-related severe toxicity. Collectively, this study provides a promising approach for safe and effective chemotherapy via MMAE-based prodrug nanoparticles, which may open new avenues for advanced drug design for translational nanomedicine.